Attack parameter dependent resilient H∞ path-following control design for autonomous vehicles under cyber attacks. (June 2023) - Hu, Songlin; Yu, Wenxi; Yang, Jinghui; Chen, Xiaoli; Xie, Xiangpeng; Ma, Yong
Abstract: Autonomous vehicles typically transmit information over wireless communication network, which is vulnerable to malicious cyber attacks and poses huge security threats for autonomous vehicles. To address these challenges, this paper is concerned with resilient H ∞ path-following control problem for autonomous vehicles under false data injection (FDI) attacks and denial-of-service (DoS) attacks, simultaneously. Firstly, a novel observer is constructed to estimate both sensor FDI attack signal and system state. An attack parameter dependent time-varying piecewise Lyapunov function is constructed to ensure stability of the underlying system. Then, a resilient H ∞ path-following control scheme is developed to suppress the impact of FDI attacks and external interference despite the presence of intermittent DoS attacks. The design criterion of resilient controller is derived to assure the exponential stability of the closed-loop system and maintain the desired H ∞ performance. Finally, simulation studies are carried out to verify the efficiency and merits of the developed results.